POTENSI PENGEMBANGAN PETERNAKAN SAPI POTONG DI KECAMATAN TANJUNG BINTANG KABUPATEN LAMPUNG SELATAN - Heru Yoga Prawira; Muhtarudin ,; Rudy Sutrisna (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
This study was conducted in February 2015 at Tanjung Bintang District South Lampung Regency. This study aimed to determine development of beef cattle potency by environment, natural resources, human resources, technology, and formulate strategies development of beef cattle to apply in Tanjung Bintang District. Interview farmer as much as 50 people from five village: Jati Baru, Jati Indah, Budilestari, Srikaton and Trimulyo. This study used survey method and than descriptive and SWOT analysis. The result of this study showed that Tanjung Bintang District have good environment potency and natural resources but has the human resources potency and input technology adverse in development of beef cattle. Alternative strategy can be implemented in Tanjung Bintang District is improving farmer knowledge in beef cattle farming specially innovative feed processing technology input through counseling and training feed processing and capital aid to increase business of beff cattle. Keywords: Alternative strategy, beef cattle, development of beef cattle potency.